Desarrollo de una Aplicación Móvil multiplataforma de Delivery para farmacias Cruz Azul utilizando Flutter y NestJS - Farfan Miranda, Antonio Adolfo (2025)
The research project aimed to develop a cross-platform mobile application to enhance the purchasing and delivery experience of pharmaceutical products for Cruz Azul pharmacies. This application allows users to browse available products, place orders, manage secure payments, and track deliveries in real-time, thereby refining accessibility and efficiency in acquiring medications.For the application's development, a DevOps environment was employed, using tools such as Git, GitHub, Jenkins, Docker, and SonarQube, which eased continuous integration, process automation, and ongoing software improvement. Technologies such as JWT (JSON Web Token) were used for secure user authentication, Flutter for the frontend development, and NestJS for the backend, resulting in a secure, scalable application with an intuitive user interface.The project adopted the Mobile-D agile method, specifically designed for mobile application development, enabling efficient requirements management and quick adaptability to changes. Additionally, the FURPS quality model was applied to evaluate key aspects of the software, including performance, usability, and reliability. Real-time simulation tests were conducted using Apache JMeter to assess indicators such as response time, resource consumption, and availability.The results proved that the application meets the highest quality standards, excelling in performance, security, and user experience. This makes it a highly efficient technological solution for improving pharmaceutical delivery processes and improving customer service